Liver Surgery for Hepatocellular Carcinoma: Laparoscopic versus Open Approach - C. G. Ker; J. S. Chen; K. K. Kuo; S. C. Chuang; S. J. Wang; W. C. Chang; K. T. Lee; H. Y. Chen; C. C. Juan (International Journal of Hepatology)
In this study, we try to compare the benefit of laparoscopic versus open operative procedures. Patients and Methods. One hundred and sixteen patients underwent laparoscopic liver resection (LR) and another 208 patients went for open liver resection (OR) for hepatocellular carcinoma (HCC). Patients' selection for open or laparoscopic approach was not randomized. Results. The CLIP score for LR and OR was 0.59 ± 0.75 and 0.86 ± 1.04, respectively, (𝑃=.016). The operation time was 156.3 ± 308.2 and 190.9 ± 79.2 min for LR and OR groups, respectively. The necessity for blood transfusion was found in 8 patients (6.9%) and 106 patients (50.9%) for LR and OR groups. Patients resumed full diet on the 2nd and 3rd postoperative day, and the average length of hospital stay was 6 days and 12 days for LR and OR groups. The complication rate and mortality rate were 0% and 6.0%, 2.9% and 30.2% for LR and OR groups, respectively. The 1-yr, 3-yr, and 5-yr survival rate was 87.0%, 70.4%, 62.2% and 83.2%, 76.0%, 71.8% for LR and OR group, respectively, of non-significant difference. From these results, HCC patients accepted laparoscopic or open approach were of no significant differences between their survival rates.